A World of Cobenefits: Solving the Global Nitrogen Challenge. Issue 8 (4th August 2019) - Houlton, Benjamin Z.; Almaraz, Maya; Aneja, Viney; Austin, Amy T.; Bai, Edith; Cassman, Kenneth G.; Compton, Jana E.; Davidson, Eric A.; Erisman, Jan Willem; Galloway, James N.; Gu, Baojing; Yao, Guolin; et al.
Abstract: Nitrogen is a critical component of the economy, food security, and planetary health. Many of the world's sustainability targets hinge on global nitrogen solutions, which, in turn, contribute lasting benefits for (i) world hunger; (ii) soil, air, and water quality; (iii) climate change mitigation; and (iv) biodiversity conservation. Balancing the projected rise in agricultural nitrogen demands while achieving these 21st century ideals will require policies to coordinate solutions among technologies, consumer choice, and socioeconomic transformation. Key Points: Global nitrogen solutions generate cobenefits for (i) world hunger, (ii) pollution, (iii) climate change, and (iv) biodiversity We provide the most comprehensive, solutions‐focused strategy for global nitrogen to date We call for an IPCC‐type organization focused on global nitrogen issues and public‐private partnerships to scale solutions